Routledge handbook of state recognition - Visoka, Gëzim; Doyle, John; Newman, Edward (Routledge handbooks., 2020)
This new handbook provides a comprehensive and multidisciplinary overview of the theoretical and empirical aspects of state recognition in international politics. Although the recognition of states plays a central role in shaping global politics, it remains an under-researched and widely dispersed subject. Coherently and innovatively structured, the handbook brings together a group of international scholars who examine the most important theoretical and comparative perspectives on state recognition, including debates about pathways to secession and self-determination, the broad range of actors and strategies that shape the recognition of states and a significant number of contemporary case studies